1987
DOI: 10.1002/ar.1092180103
|View full text |Cite
|
Sign up to set email alerts
|

3H‐mannose utilization by fibroblasts of the periodontal ligament

Abstract: The synthesis, intracellular translocation, and secretion of mannose-containing glycoproteins(s) by periodontal ligament fibroblasts have been investigated by means of electron microscopic radioautography. Tritiated mannose was administered to young mice via jugular vein, and radioautographs were prepared at 5, 10, 20, and 35 minutes, 4 and 8 hours after injection. Analysis of electron microscopic radioautographs revealed a maximum labeling (94%) with 3H-mannose of the rough endoplasmic reticulum at 5 minutes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Free polymannose-type oligosaccharides incubated with liver cells have previously been shown to predominantly accumulate in lysosomes 46 . To quantify mannose uptake, radiolabeled probes have been used effectively 26 , 47 . We demonstrated that unmetabolized mannose is mainly located in the lysosome of colonic epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Free polymannose-type oligosaccharides incubated with liver cells have previously been shown to predominantly accumulate in lysosomes 46 . To quantify mannose uptake, radiolabeled probes have been used effectively 26 , 47 . We demonstrated that unmetabolized mannose is mainly located in the lysosome of colonic epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously studied the utilization of [3H]mannose by periodontal ligament fibroblasts by electron microscopic radioautography (Cho and Garant, 1987). The routes and time periods for the intracellular translocation of mannose-containing glycoproteins in the periodontal ligament fibroblasts were found to be comparable to those for procollagen (Cho and Garant, 1981b, c).…”
Section: Discussionmentioning
confidence: 99%